2014
DOI: 10.1186/1752-1947-8-77
|View full text |Cite
|
Sign up to set email alerts
|

Currarino syndrome in an adult presenting with a presacral abscess: a case report

Abstract: IntroductionCurrarino syndrome (Currarino triad) was described in 1981 as a triad syndrome with a common embryogenesis in infants and with three characteristics: anorectal stenosis, a defect in the sacral bone, and a presacral mass. We describe here an unusual case of Currarino syndrome in an adult presenting with a presacral abscess but no meningitis.Case presentationA 32-year-old Japanese man presented with fever, arthralgia and buttock pain. A digital rectal examination showed mild rectal stenosis with loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Furthermore, meningitis is one of the most severe complications in CS and occurred in 7e11% of all cases, including familial cases in previous reports [9]. The communication between the spinal canal and the presacral tumor through the tethered cord is considered to be the cause of the patient's meningitis and spinal cord abscess [1,14,15]. The mortality due to meningitis in CS is surprisingly high at 56% [10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, meningitis is one of the most severe complications in CS and occurred in 7e11% of all cases, including familial cases in previous reports [9]. The communication between the spinal canal and the presacral tumor through the tethered cord is considered to be the cause of the patient's meningitis and spinal cord abscess [1,14,15]. The mortality due to meningitis in CS is surprisingly high at 56% [10].…”
Section: Discussionmentioning
confidence: 96%
“…It is hypothesized that meningitis is caused by a Tethered cord communicating between the presacral space and intramedullary space [1,14,15]. In severe cases, the cavity of the abscess extends to the intramedullary space and leads to a lifethreatening septic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Currarino syndrome is a rare autosomal dominant hereditary disorder [4]. Since the Currarino triad was first described by Currarino in 1981, approximately 300 cases have been reported [345]. However, the exact incidence of this condition is unknown owing to its multiple phenotypes and clinical presentations [5].…”
Section: Discussionmentioning
confidence: 99%
“…Since the Currarino triad was first described by Currarino in 1981, approximately 300 cases have been reported [345]. However, the exact incidence of this condition is unknown owing to its multiple phenotypes and clinical presentations [5]. Recent studies have reported an association between Currarino syndrome (primarily sacral agenesis) and the HLXB9 gene located on chromosome 7q36 [4].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Their occurrence in the sacral region is unusual. [ 1 2 3 4 5 6 7 8 9 ] Most of the sacral SEs have been reported either in conjunction with anterior sacral meningoceles, as a component of Currarino syndrome (CS),[ 10 11 12 13 14 ] or as sequelae to lumbar punctures. [ 9 15 ] This report of a patient with a primary, nonsyndromal sacral SE in the absence of coexistent spinal dysraphism or preceding trauma is the third of its kind in indexed literature.…”
Section: Introductionmentioning
confidence: 99%